Writing Fictional Short Stories About the Anthropocene: Effects on Students’ Futures Thinking - Hervé, Nicolas; Panissal, Nathalie (Frontiers in Education, 2022)
This article deals with the identification of some general guidelines for teaching aimed at developing futures thinking about themes of the Anthropocene. For that, we estimate such teaching activities at the intersection of socioscientific issues, environmental education, and futures education. We describe two teaching contexts designed on this principle, and centered on pupils’ writing fictional narratives, and analyze the effects on their futures thinking. The results show that it is important to design teaching activities that make it possible to think about the temporalities of processes and phenomena, and to invest relational responsibilities. In order for the pedagogical activity to take temporalities into account, we propose that the backgrounds of the futures on which the stories take place be constructed iteratively, evolving in defined time steps. Writing short stories can also allow for a deeper understanding of relational responsibilities, based more on the framework of capabilities. One perspective is to integrate fictional short stories writing into the repertoire of possible activities to be conducted in an inquiry-based pedagogy about the Anthropocene.